Platinum‐Catalyzed Cascade Rearrangement Reaction of 1, 5‐Diynyl Esters: Unusual Regioselective 1, 5‐Hydride Migration. Issue 7 (27th May 2015) - Zhu, Hui; Huang, Jiapian; Fan, Congbin; Chen, Zhiyuan
Abstract A highly regioselective sequential 1, 3‐acyloxy migration/pentannulation/1, 5‐hydride migration reaction is disclosed which provides an efficient access to (E)‐2‐vinyl‐3‐oxo‐1‐methyleneindenes under neutral and mild reaction conditions. The migrated hydrogen atom was derived from an unactivated alkyl group, and the long‐range 1, 5‐H shift was confirmed through related deuterium experiments.